Methylation of high-molecular-weight subunit RNA of feline leukemia virus. - Thomason, A R (1976)
The high-molecular-weight subunit RNA of feline leukemia virus (Rickard strain) (FeLV-R) was analyzed for the presence of methyl groups. After purification of native 50-60S FeLV-R RNA on nondenaturing aqueous sucrose density gradients. FeLV-R 28S subunit RNA, doubly labeled with [14C]uridine and [methyl-3H]methionine, was isolated by centrifugation through denaturing sucrose density gradients in dimethyl sulfoxide. As calculated from their respective 3H/14C ratios. FeLV-R 28S RNA was methylated to the same degree as host cell poly(A)+ mRNA. When the 28S FeLV-R RNA was hydrolyzed to completion with RNase T2 or alkali, all of the methyl-3H chromatographed with mononucleotides on Pellionex-WAX, a weak anion exchanger. The methyl-labeled material co-chromatographed with 6-methyladenosine if the mononucleotide fraction obtained by Pellionex-WAX chromatography was hydrolyzed to nucleosides by bacterial alkaline phosphatase or with 6-methyladenine if purine bases were released from the mononucleotides by acid hydrolysis. In another experiment in which FeLV-R 28S RNA uniformly labeled with 32P was hydrolyzed and then analyzed by Pellionex-WAX chromatography, all of the 32P label again co-chromatographed with mononucleotides. Thus FeLV-R 28S RNA does not appear to contain a 5' structure, either methylated or nonmethylated similar to those recently reported for cellular and some animal virus mRNA's.